Labelling of allergens and intolerance-causing foods in Ukraine - Dudarev, Igor (Lutsk : LNTU, 2025)
The number of consumers with food allergies or intolerances is rapidly increasing worldwide. Legislation in many countries, including Ukraine, defined a list of substances and foods that cause allergic reactions or intolerances. It also establishes requirements for allergen labelling on food packaging, which manufacturers must comply with. The purpose of this study was to determine, how food manufacturers in Ukraine indicate the presence of substances and ingredients that may cause allergic reactions and intolerances, and whether such labelling meets the requirements of Ukrainian legislation. For the label analysis, food products were grouped into 10 categories: sausages, bakery products, cookies and waffles, dairy products, sauces and mayonnaises, cheeses, snacks, instant foods, confectionery and ice creams. The study was conducted by analysing food labels from local supermarkets in Lutsk, Ukraine. It was found that the majority of the foods analysed contained allergens or ingredients that cause intolerance. Between 8% and 22% of food products in different categories did not have allergens properly identified on the labels, even though they were present. On food labels, Ukrainian manufacturers mainly used bold type to highlight substances and ingredients that may cause allergies and intolerances (74.0-100.0% of products). Only 4.0-28.3% of product labels used capital letters to highlight these substances and ingredients. Text highlighting through colour, style, background and underlining was much less common and was most often combined with bold text. The terms “contains” and “may contain traces of” appeared on the labels of 6.0-36.0% and 6.0-76.1% of foods, respectively. The most common ingredients on the labels of the food products analysed were processed cereal products containing gluten, eggs, milk or dairy products, processed soy products, peanuts, and nuts. The results of the analysis showed that Ukrainian producers generally comply with Ukrainian legislation regarding the labelling of substances or ingredients in food products that may cause allergic reactions or intolerance.
Keywords: allergy; consumer protection; label requirements; ingredient disclosure; regulatory standards